The Mistaken Identification of “The West” with “Modernity” - John Obert Voll (International Institute of Islamic Thought, 1996)
The relationships between Islam and the West are complex. Even the perceptions of those relations have an important impact on the nature of the interactions. If the basic images that are used in discussing “Islam and the West” are themselves ill-defiied or viewed in inconsistent ways, the relationships themselves are affected in sometimes dangerous ways. Inconsistent and contradictory terms of analysis can lead to misunderstanding and conflict. One of the most frequent conceptual mistakes made in discussing Islam and the West in the modem era is the identification of “the West” with “modemity.” This mistake has a significant impact on the way pee ple view the processes of modernization in the Islamic world as well as on the way people interpret the relationships between Islam and the West in the contemporary era. The basic generalizations resulting from the following analysis can be stated simply: 1) “modernity“ is not uniquely “western”; 2) “the West” is not simply “modernity”; and 3) the identifixation of “the West” with “modemity” has important negative consequences for understanding the relationships between Islam and the West. Modernity and the West are two different concepts and historic entities. To use the terms interchangeably is to invite unnecessary confusion and create possible conflict’and inconsistency. This article will address the problem of definition and the application of the defined terms to interpreting actual experiences and relationships. Understanding the difficulties raised by the identification of the West with modernity involves a broader analysis within the framework of world history and global historical perspectives. In such an analysis, ...